Elevated Maternal Leptin Levels and Higher Birth Weight in Obese Mothers Compared with Normal-weight Mothers - Rezi Liawati; Yusrawati Yusrawati; Nelmi Silvia (Cell and BioPharmaceutical Institute, 2026)
Background: Maternal obesity is associated with disrupted metabolic regulation, including elevated leptin levels that may affect fetal growth. Previous studies have reported mixed findings on maternal and cord blood leptin concentrations, with some showing higher leptin levels in infants born to obese mothers, while others found no significant differences. Associations between maternal obesity and neonatal outcomes have also been inconsistent. This study aims to generate new evidence from an Indonesian cohort by comparing maternal and cord blood leptin levels, as well as neonatal outcomes, between obese and normal-weight mothers.Materials and Methods: Analytical cross-sectional study enrolled 30 obese and 30 normal-weight mothers from two hospitals in Padang, Indonesia. Maternal and cord blood samples were collected at delivery, and leptin levels were measured using ELISA. Ethical approval and informed consent were obtained. Neonatal outcomes included birth weight, length, head circumference, and ponderal index. Data were analyzed using Independent Samples t-test or Mann–Whitney U test, with p<0.05 considered statistically significant. Results: Maternal leptin levels were significantly higher in obese mothers than in normal-weight mothers (70.8±39.0 vs. 44.5±42.5 ng/mL; p=0.002). Cord blood leptin levels did not differ between groups (19.7±14.9 vs. 16.1±17.5 ng/mL; p=0.394). Neonates of obese mothers had higher birth weight (p=0.003), while other anthropometric measures were similar.Conclusion: Maternal obesity was associated with elevated maternal leptin levels and increased neonatal birth weight, while cord blood leptin did not differ significantly between groups. These findings suggest that maternal leptin reflects maternal metabolic status rather than fetal growth.Keywords: maternal leptin, cord blood leptin, obesity, pregnancy, neonatal outcome